Religious affiliation, religiosity and health behaviors among high school students in Jakarta, Indonesia - Mochamad Iqbal Nurmansyah; Miftahul Jannah; Emma Rachmawati; Iram Barida Maisya (International Journal of Public Health Science (IJPHS), 2020)
This study aimed to determine a relationship between religious affiliation, religiosity and health behaviors among high school students in Jakarta, Indonesia. This cross-sectional study was conducted in 9 high schools in Jakarta, Indonesia. A total of 767 respondents joined this study.  A multivariate analysis was conducted to determine the associations between dependent and independent variables by adjusting age, sex, school type and economic status. Lower non-organized religious activity had a significant association with higher addictive behaviors (AOR: 0.577 95% CI: 0.340-0.979). In case of nutrition behaviors, there were no significant associations among all aspects of religiosity. Lower organized religious activity was associated with physical inactivity (AOR: 0.323 95% CI: 0.170-0.614). In addition, lower non-organized and intrinsic religiosity had significant association with lower personal hygiene behaviors (AOR= 0.433 95% CI: 0.272-0.688; AOR: 0.436 95% CI: 0.198-0.958). Students with higher religiosity tend to engage less in risky health behaviors. Religious leaders and organizations may be engaged in health promotion activities to disseminate and create better understanding of religious values and beliefs regarding health behaviors.